1994
DOI: 10.1002/j.1460-2075.1994.tb06392.x
|View full text |Cite
|
Sign up to set email alerts
|

A single amino acid substitution in the exoplasmic domain of the human growth hormone (GH) receptor confers familial GH resistance (Laron syndrome) with positive GH-binding activity by abolishing receptor homodimerization.

Abstract: Growth hormone (GH) elicits a variety of biological activities mainly mediated by the GH receptor (GHR), a transmembrane protein that, based on in vitro studies, seemed to function as a homodimer. To test this hypothesis directly, we investigated patients displaying the classic features of Laron syndrome (familial GH resistance characterized by severe dwarfism and metabolic dysfunction), except for the presence of normal binding activity of the plasma GH‐binding protein, a molecule that derives from the exopla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
51
0
2

Year Published

1998
1998
2010
2010

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(56 citation statements)
references
References 44 publications
(24 reference statements)
3
51
0
2
Order By: Relevance
“…Patients with atypical forms of GHIS have detectable plasma GHbinding activity, associated with complete or partial GHIS (146,167). However, molecular analyses of the phenotype with complete GHIS have revealed the existence of a missense mutation in the exoplasmic domain mainly located in exons 2-7 that impairs first receptor action by affecting GH binding and second, therefore, abolishes receptor homodimerization, thereby providing in vivo evidence for the critical role of the dimerization process in the growth-promoting action of GH (168). Similarly, missense mutations in the cytoplasmic region, which would not be expected to affect GH-binding activity, should contribute to the identification of other important domains involved in signal transduction.…”
Section: Gh Insensitivity and Defects In The Ghr Genementioning
confidence: 99%
See 1 more Smart Citation
“…Patients with atypical forms of GHIS have detectable plasma GHbinding activity, associated with complete or partial GHIS (146,167). However, molecular analyses of the phenotype with complete GHIS have revealed the existence of a missense mutation in the exoplasmic domain mainly located in exons 2-7 that impairs first receptor action by affecting GH binding and second, therefore, abolishes receptor homodimerization, thereby providing in vivo evidence for the critical role of the dimerization process in the growth-promoting action of GH (168). Similarly, missense mutations in the cytoplasmic region, which would not be expected to affect GH-binding activity, should contribute to the identification of other important domains involved in signal transduction.…”
Section: Gh Insensitivity and Defects In The Ghr Genementioning
confidence: 99%
“…There are, however, several cases of GHR defects reported associated with normal or raised GHBP levels in patients with mutations involving extracellular, transmembrane or intracellular domains. Duquesnoy et al (168) reported a D152H mutation in exon 6 causing positive GH-binding activity but abolished GHR homodimerization. In contrast, in two subjects with severe GHIS caused by a 5 0 splice donor site mutation within IVS-8, serum GHBP was massively increased, because the mutation resulted in a truncated GHR molecule (175).…”
Section: Gh Insensitivity and Defects In The Ghr Genementioning
confidence: 99%
“…Such mutations have tended to result in severe, if not complete, loss of GH binding by the receptor, with the consequent loss of essentially all GH-mediated action. Interestingly, mutations affecting the extracellular domain which preserve GH binding have been reported, but such mutations impact GH action, for example, by inhibiting dimerization of the receptor, a step necessary for GH signal transduction (8).…”
mentioning
confidence: 99%
“…The GHR protein is an integral cell membrane molecule that, in humans, contains 638 residues (including a membrane signal peptide of 18 residues); it consists of an extracellular hormone-binding domain of 246 amino acids, a single transmembrane domain, and a cytoplasmic domain of 350 residues (13). Upon binding to the growth hormone, the GHR molecule can form homodimers (14) that are essential to receptor activation (15,16), thereby mediating the well known biological effects of growth hormone. The critical importance of the receptor in the control of body growth was clearly demonstrated by the description of numerous GHR mutations in patients with Laron syndrome, a severe growth hormone-resistant short stature condition transmitted as an autosomal recessive trait (17).…”
mentioning
confidence: 99%